Bernard of Clairvaux : Sermons for the Autumn Season - Bernard, of Clairvaux, Saint, 1090 or 1091-1153 (Book collections on Project MUSE., 2016)
On the anniversary of the dedication of the monastery church at Clairvaux, Saint Bernard spoke to the community to explain the meaning of the feast: "What sanctity can these stones have that we should celebrate their festival? They do indeed have sanctity, but it is because of your bodies. . . .Your bodies are holy because of your souls, and this house is holy because of your bodies." The thirty-eight sermons in this volume carry forth this theme, revealing the holiness of the monastic life as monks alternate through the rhythm of the day and the year between the opus Dei and manual labor, journeying faithfully through life to death and the transitus to glory. The twelfth-century Ecclesiastica Officia of the Cistercian Order required abbots to speak formally to their communities in chapter on seventeen fixed days, mostly liturgical feasts. This volume witnesses to Bernard's fulfillment of this requirement and includes sermons for the Assumption and Nativity of the Virgin and the Feast of All Saints, sermons devoted to the feasts of particular saints celebrated during the autumn months, sermons for the time of harvest, and funeral sermons that look forward to the eternal joy in the communion of saints. (Publisher).